The polyphasic analysis of two native Raphidiopsis isolates supports the unification of the genera Raphidiopsis and Cylindrospermopsis (Nostocales, Cyanobacteria) - Aguilera, Anabella (2018)
Raphidiopsis and Cylindrospermopsis are planktic, freshwater bloom-forming cyanobacteria of great concern to human health due to the production of potent cyanotoxins. The presence (in Cylindrospermopsis) or absence (in Raphidiopsis) of heterocytes is the traditional character used to distinguish them. This has led to misidentifications and to questions about the validity of the genus Raphidiopsis. We studied two strains of R. mediterranea isolated from Argentinean shallow lakes using a polyphasic approach that included the morphological description of the natural populations and their ultrastructural, physiological and molecular characterisation. Heterocyte differentiation was not observed in the field or in cultures of R. mediterranea submitted to nitrogen deprivation. These results support the occurrence of stable native populations of R. mediterranea without heterocytes, which would not be a part of the Cylindrospermopsis complex life cycle. Based on 16S rRNA, 16S–23S ITS, and cpcBA-IGS sequences, these two genera are virtually identical. Thus, strains of Raphidiopsis and Cylindrospermopsis make up a monophyletic lineage in all phylogenetic reconstructions. Furthermore, the 16S–23S ITS secondary structure provided further evidence that these two genera cannot be separated. The intermixed position in the trees points to several losses of heterocytes during the evolution of these cyanobacteria. We conclude that these two genera should not be regarded as separate and distinct generic units and propose their unification under the name Raphidiopsis, respecting the principle of priority. Accordingly, we revisited and emended the description of Raphidiopsis.